Fermentative production and direct extraction of (−)-α-bisabolol in metabolically engineered Escherichia coli. Issue 1 (December 2016) - Han, Gui; Kim, Seong; Yoon, Paul; Kang, Younghwan; Kim, Byoung; Fu, Yaoyao; Sung, Bong; Jung, Heung; Lee, Dae-Hee; Kim, Seon-Won; Lee, Seung-Goo
Abstract Background (−)-α-Bisabolol, also known as levomenol, is an unsaturated sesquiterpene alcohol that has mainly been used in pharmaceutical and cosmetic products due to its anti-inflammatory and skin-soothing properties. (−)-α-Bisabolol is currently manufactured mainly by steam-distillation of the essential oils extracted from the Brazilian candeia tree that is under threat because its natural habitat is constantly shrinking. Therefore, microbial production of (−)-α-bisabolol plays a key role in the development of its sustainable production from renewable feedstock. Results Here, we created anEscherichia coli strain producing (−)-α-bisabolol at high titer and developed an in situ extraction method of (−)-α-bisabolol, using natural vegetable oils. We expressed a recently identified (−)-α-bisabolol synthase isolated from German chamomile (Matricaria recutita ) (titer: 3 mg/L), converted the acetyl-CoA to mevalonate, using the biosynthetic mevalonate pathway (12.8 mg/L), and overexpressed farnesyl diphosphate synthase to efficiently supply the (−)-α-bisabolol precursor farnesyl diphosphate. Combinatorial expression of the exogenous mevalonate pathway and farnesyl diphosphate synthase enabled a dramatic increase in (−)-α-bisabolol production in the shake flask culture (80 mg/L) and 5 L bioreactor culture (342 mg/L) of engineeredE. coli harboring (−)-α-bisabolol synthase. Fed-batch fermentation using a 50 L fermenter was conducted after optimizing culture conditions, resulting in efficient (−)-α-bisabolol production with a titer of 9.1 g/L. Moreover, a green, downstream extraction process using vegetable oils was developed for in situ extraction of (−)-α-bisabolol during fermentation and showed high yield recovery (>98%). Conclusions The engineeredE. coli strains and economically viable extraction process developed in this study will serve as promising platforms for further development of microbial production of (−)-α-bisabolol at large scale.